Keberlanjutan Pembangunan Kawasan Perkotaan Berbasis Penyiapan Ruang Terbuka Hijau di Kota Parepare: Studi Kasus: Kecamatan Bacukiki, Kota Parepare - Azilia, Andi Mirza; Selintung, Mary; Syafri, Syafri (Postgraduate Bosowa University, 2023)
Isu keberlanjutan menjadi populer, pemicunya adalah fenomena pemanasan global yang mengkawatirkan keberlangsungan kehidupan di Bumi. Gejalanya adalah meningkatnya suhu rata-rata di Bumi yang disebabkan oleh efek gas rumah kaca. Tujuan penelitian adalah untuk mengetahui capaian pemenuhan Ruang Terbuka Hijau di Kawasan Perkotaan Parepare di Kecamatan Bacukiki. Metodologi penelitian yang digunakan didasarkan pada pendekatan kualitatif melalui interpertasi data sekunder yang tersedia dan dapat diakses oleh umum. Ruang terbuka hijau (RTH) menjadi salah satu fungsi penting dalam alokasi peruntukan setiap wilayah yang berfungsi menjaga keseimbangan ekosistem. Sesuai ketentuan peraturan perundangan, ditetapkan besaran 30% untuk fungsi RTH dengan proporsi 20% RTH publik dan 10% RTH privat. Dalam pelaksanaannya sebagian besar wilayah belum berhasil memenuhi capaian sesuai besaran yang ditetapkan. Penelitian ini bertujuan untuk mengetahui besaran RTH dan mengidentifikasi strategi yang dilakukan dalam rangka memenuhi penyediaan RTH untuk mencapai target yang disyaratkan. Menggunakan pendekatan deskriptif, penelitian ini dilakukan untuk mendapatkan dua jenis data mencakup data luas eksisting RTH publik dan data strategi penyediaan RTH. Data luas RTH diperoleh melalui interpretasi citra yang didigitasi dan divalidasi dengan ground survey, sementara data strategi penyediaan RTH diperoleh melalui sumber sekunder dari laporan Dinas Pekerjaan Umum dan Tata Ruang Provinsi Sulawesi Selatan Tahun 2021. Maka diperlukan strategi untuk meningkatkan RTH dengan mulai berpikir alternatif melalui peningkatan RTH privat dan pemenuhan RTH Publik. The issue of sustainability has become popular, the trigger is the phenomenon of global warming which is worrying about the continuity of life on Earth. The symptom is an increase in the average temperature on Earth caused by the effects of greenhouse gases. The aim of the study is to determine the achievement of fulfilling Green Open Space in the Parepare Urban Area in Bacukiki District. The research methodology used is based on a qualitative approach through interpretation of secondary data that is available and accessible to the public. Green open space is an important function in the allocation of land use for each area which functions to maintain ecosystem balance. In accordance with statutory provisions, the amount is set at 30% for green open space functions with a proportion of 20% public green open space and 10% private green open space. In its implementation, most regions have not succeeded in meeting the achievements according to the stipulated amounts. This research aims to determine the size of green open space and identify the strategies carried out to fulfill the provision of green open space to achieve the required targets. Using a descriptive approach, this research was carried out to obtain two types of data including data on the existing area of public green open space and data on strategies for providing green open space. Data on the area of green open space was obtained through digitized image interpretation and validated with a ground survey, while data on the strategy for providing green open space was obtained through secondary sources from the 2021 South Sulawesi Provincial Public Works and Spatial Planning Service report. Strategy to increase the area of public green open space through planting trees along roads, land acquisition for green areas in settlements, and clearance of river borders from buildings for re-function as green open spaces. The increase has been quite slow, and the area obtained has not been able to increase the green open spaces significantly. Another strategy is needed to increase green open space by starting to think about alternatives by increasing private green open space